KOMUNIKASI KAUM TAREKAT STUDI TENTANG POLA-POLA KOMUNIKASI DALAM KELOMPOK TAREKAT QADIRIYAH NAQSYABANDIYAH DI PESANTREN SURYALAYA TASIKMALAYA - Asep Shalahudin (Sekolah PascaSarjana Unpad, 2013)
This study is qualitative using phenomenological, symbolic interaction, and hermeneutic approaches. Based on the proposed descriptions, the author found that communications in Tarekat Qadiriyah Naqsyabandiyah Suryalaya, phenomenologically, describe a communication event which reflects an esoteric rite identity of religious doctrine (Islam). This esoteric rite identity of religious doctrine is formulated in symbolic form and addressed as a medium to achieve the high potential and the purpose in life. The symbol formation in this tarekat community serves as a fundamental process of determinations, thoughts, and actions. Through this symbolization as well, Tarekat Qadiriyah Naqsyabandiyah community communicates, as reflected in their convocation ceremony. This tarekat ceremony shows objective symbol orders. These symbols not only express a behavior andfeeling but also form a personal disposition from brothers (ikhwan) followed their teacher models (mursyid) or saint models orwali (holy man) derived through mythological stories. Tarekat Qadiriyah Naqsyabandiyah gives the meaning of growingcommunication as the complex one. The meaning and the comprehension of communication holds subjectively, humanistically, aesthetically, philosophically, and religious esoteric oriented. Ikhwan